ANALISIS TINGKAT KENYAMAN TERMAL DI KOTA PALEMBANG BERDASARKAN INDEX THI (TEMPERATURE HUMIDITY INDEX) - Shelin Melinda (Megasains, 2022)
Population growth in Palembang, South Sumatra Province is increasing, statistical data shows an increase in the population in 2020 to 1,868,848 people. The increase in population is one of the triggers for land expansion in development, such as residential areas and a reduction in urban green spaces. The increase in population and land expansion in Palembang without being balanced with the environmental balance will cause urban warming caused by changes or increases in air temperature which causes discomfort in an area. This study aims to determine how the level of thermal comfort and its tendency in Palembang using the THI index. In this study, two climate variables were used to calculate the THI index, namely daily average air temperature and daily relative humidity during the period 1991 - 2020 from the Palembang Climatology BMKG Station. Based on the results of the THI index, in general the comfort level is dominated by the partial comfort category as much as 73.9% or 270 days / year and the THI tends to increase every year with an increase in temperature of 0.03 ° C / year.